Identification of the autophagy pathway in a mollusk bivalve, Crassostrea gigas. Issue 11 (1st November 2020) - Picot, Sandy; Faury, Nicole; Arzul, Isabelle; Chollet, Bruno; Renault, Tristan; Morga, Benjamin
ABSTRACT: The Pacific oyster, Crassostrea gigas, is a mollusk bivalve commercially important as a food source. Pacific oysters are subjected to stress and diseases during culture. The autophagy pathway is involved in numerous cellular processes, including responses to starvation, cell death, and microorganism elimination. Autophagy also exists in C. gigas, and plays a role in the immune response against infections. Although this process is well-documented and conserved in most animals, it is still poorly understood in mollusks. To date, no study has provided a complete overview of the molecular mechanism of autophagy in mollusk bivalves. In this study, human and yeast ATG protein sequences and public databases (Uniprot and NCBI) were used to identify protein members of the C. gigas autophagy pathway. A total of 35 autophagy related proteins were found in the Pacific oyster. RACE-PCR was performed on several genes. Using molecular (real-time PCR) and protein-based (western blot and immunohistochemistry) approaches, the expression and localization of ATG12, ATG9, BECN1, MAP1LC3, MTOR, and SQSTM1, was investigated in different tissues of the Pacific oyster. Comparison with human and yeast counterparts demonstrated a high homology with the human autophagy pathway. The results also demonstrated that the key autophagy genes and their protein products were expressed in all the analyzed tissues of C. gigas . This study allows the characterization of the complete C. gigas autophagy pathway for the first time. Abbreviations: ATG: autophagy related; Atg1/ULK: unc-51 like autophagy activating kinase; ATG7: autophagy related 7; ATG9: autophagy related 9; ATG12: autophagy related 12; BECN1: beclin 1; BSA: bovine serum albumin; cDNA: complementary deoxyribonucleic acid; DNA: deoxyribonucleic acid; GABARAP: GABA type A receptor-associated protein; IHC: immunohistochemistry; MAP1LC3/LC3/Atg8: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; NCBI: national center for biotechnology information; ORF: open reading frame; PBS: phosphate-buffered saline; PCR: polymerase chain reaction; PtdIns3K: class III phosphatidylinositol 3-kinase; RACE-PCR: rapid amplification of cDNA-ends by polymerase chain reaction; RNA: ribonucleic acid; SQSTM1: sequestosome 1; Uniprot: universal protein resource; WIPI: WD repeat domain, phosphoinositide interacting.